2015
DOI: 10.1002/dta.1921
|View full text |Cite
|
Sign up to set email alerts
|

Drugs of abuse in maternal hair and paired neonatal meconium: an objective assessment of foetal exposure to gestational consumption

Abstract: In a prospective sample of 80 mother-infant dyads, we investigated whether drugs of abuse in maternal hair measured during the pregnancy trimesters were also present in neonatal meconium. Principal drugs of abuse were analyzed in the three consecutive maternal hair segments and meconium samples by ultra-performance liquid chromatography tandem mass spectrometry assay. Of the 80 mothers, 32 (40%) presented one or more hair shafts with at least one of the analyzed drugs of abuse and/or its metabolites. The drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 21 publications
3
23
0
5
Order By: Relevance
“…Frequent and chronic exposure is necessary to produce meconium positive results. [21,28] Our results are in agreement with these previous studies. Meconium only was positive if a frequent drug abuse was documented by hair analysis during the whole pregnancy for cocaine, opioids and methadone, especially during the third trimester.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Frequent and chronic exposure is necessary to produce meconium positive results. [21,28] Our results are in agreement with these previous studies. Meconium only was positive if a frequent drug abuse was documented by hair analysis during the whole pregnancy for cocaine, opioids and methadone, especially during the third trimester.…”
Section: Discussionsupporting
confidence: 94%
“… Previous studies also showed that not just the timing but also the frequency of drug exposure was critical to be able detect drugs in meconium. Frequent and chronic exposure is necessary to produce meconium positive results . Our results are in agreement with these previous studies.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Quanto ao uso de drogas lícitas não prescritas e/ou ilícitas, estudo realizado nos Estados Unidos estima as taxas de pré-natal de crianças expostas às drogas de abuso de 6% a 40% de todos os nascidos vivos (MASSACHUSETTS GENERAL HOSPITAL, 2014). Na Espanha, a referida taxa é em torno de 40% (JOYA et al, 2016). No Brasil, estudos revelam taxa de 7,82% a 19% dependendo do método e instrumento utilizado (KASSADA et al, 2013; valor próximo ao encontrado na presente pesquisa (19,5%).…”
Section: Prevalência Do Uso De Medicamentosunclassified